2010
DOI: 10.1093/cercor/bhq096
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Contributions of Left and Right Dorsolateral Prefrontal Cortex in Planning

Abstract: It is well established that the mid-dorsolateral prefrontal cortex (dlPFC) plays a critical role in planning. Neuroimaging studies have yielded predominantly bilateral dlPFC activations, but the existence and nature of functionally specific contributions of left and right dlPFC have remained elusive. In recent experiments, 2 independent parameters have been identified which substantially determine planning: 1) the degree of interdependence between consecutive steps (search depth) and 2) the degree to which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
179
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 196 publications
(190 citation statements)
references
References 76 publications
8
179
1
2
Order By: Relevance
“…This supports the conclusion that while problems may vary in difficulty, the differences in the problems considered here do not reflect a critical dimension when it comes to differentially engaging specific executive functions. Kaller et al (2011b) came to a similar conclusion in motivating their imaging study of performance on a variant of the ToL. They argued that the critical dimensions were not the number of moves required or the presence of superficially tempting moves per se, but subgoal order ambiguity and the need for intermediate moves.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…This supports the conclusion that while problems may vary in difficulty, the differences in the problems considered here do not reflect a critical dimension when it comes to differentially engaging specific executive functions. Kaller et al (2011b) came to a similar conclusion in motivating their imaging study of performance on a variant of the ToL. They argued that the critical dimensions were not the number of moves required or the presence of superficially tempting moves per se, but subgoal order ambiguity and the need for intermediate moves.…”
Section: Discussionmentioning
confidence: 84%
“…This is not the case for "flat" target states, where one disk is on each peg, and where the order in which subgoals must be achieved so as to minimise total moves is ambiguous. The tower/flat distinction applies equally to the ToL as it does to the ToH (Waldau, 1999;Kaller et al, 2008;Kaller et al, 2011a), and as noted in the introduction, Kaller et al (2011b) found that problems with ambiguous subgoal ordering engage left lateral PFC relatively more than those without (while problems that require intermediate moves activated right lateral PFC more than those that did not). Ambiguous subgoal ordering again implies the need for a switching function: successful solution of such problems will require considering different orderings of the subgoals, and hence switching between subgoals when planning moves.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations